2021
DOI: 10.1002/cncr.33678
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in pediatric cancer incidence among children and young adults in the United States by single year of age

Abstract: BACKGROUND:Incidence rates of pediatric cancers in the United States are typically reported in 5-year age groups, obscuring variation by single year of age. Additionally, racial and ethnic variation in incidence is typically presented in broad categories rather than by narrow age ranges. METHODS: The Surveillance, Epidemiology, and End Results (SEER) 18 data (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) were examined to calculate frequencies and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 51 publications
3
31
1
Order By: Relevance
“…Similar differences were found when comparing 12.5-year survival rates [24]. Marcotte found the incidence of leukemias to be higher in White children when compared to both Black and Asian/Pacific Islander children [25].…”
Section: Susceptibility To Zoonoses By Racesupporting
confidence: 67%
See 2 more Smart Citations
“…Similar differences were found when comparing 12.5-year survival rates [24]. Marcotte found the incidence of leukemias to be higher in White children when compared to both Black and Asian/Pacific Islander children [25].…”
Section: Susceptibility To Zoonoses By Racesupporting
confidence: 67%
“…Within the pediatric population, regarding racial and ethnic minority children, we found that compared to non-Hispanic White childhood cancer patients, Black and Hispanic patients had worse survival for all cancers combined, leukemias and lymphomas, brain tumors, and solid tumors [21][22][23][24][25].…”
Section: Susceptibility To Zoonoses By Racementioning
confidence: 88%
See 1 more Smart Citation
“…Adjustment for race/ethnicity was not possible since registration on race/ethnicity is not allowed in the Nordic countries. It has been reported that non-white children and young adults might have lower rates of some childhood cancers [ 57 ]. The percentage of mother’s country of birth being outside the Nordic countries was however low and similar in ART and spontaneous conception in an earlier publication from CoNARTaS [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies of childhood cancer often rely on SEER and other state-based cancer registries. [16][17][18] Although these cases are representative of the underlying population, investigations are often limited by the level of information captured by these surveillance programs. For example, detailed treatment histories and refined diagnosis information may not be readily available.…”
Section: Discussionmentioning
confidence: 99%